Konfigurasi politik hukum ekonomi syariah di Indonesia - Fauzan Ali Rasyid (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
The development of Islam in Indonesia has been integrated within social, legal, politics, and economicvalues, which is framed in any social changes. This study will be focused on the relationship betweennational political configuration and the regulation of sharia economic compilation. Based on thisassumption, I would like to propose the question, is it existence resulted by the Muslim aspiration andIslamic political party supports or more influenced by global economic changes? This study is part ofpolitical law as well as sharia economic of political law. The institutionalization of sharia economic lawis a necessity because of several reasons: First, the highly awareness of muslim to implement shariavalues in a life that are popular and socialized; Second, the growth of sharia financial institutions, bothsharia banking and non-banking institutions, and Third, the existence of sharia regional provisions(Perda Syariah).There is highly significant correlation at national and international political changestowards sharia economic law institutionalized as well as the existence of Islamic political parties orpolitical parties based on Muslims. Finnaly, the institutionalization of sharia economic law can not beseparated from the existence of Indonesia Muamalat Bank (BMI) in 1991 that regulated under the Lawof Banking Number 7 of 1992 and the Goverment Regulation Number 72 of 1992. These regulationsare introducing the principle of profit and loss-sharing in sharia bank. In refomulation period, theGoverment has amanded that Law Number 21 of 2008. Because of these regulations, sharia bank ismore improve and implements many principles such as Sharia Insurance, Rahn, Mutual Funds, CapitalMarkets, Financial Corporates based on sharia principles, etc.